Everyday aesthetics - Saito, Yuriko (Oxford University Press, 2007)
Everyday aesthetic experiences and concerns occupy a large part of our aesthetic life. However, because of their prevalence and mundane nature, we tend not to pay much attention to them, let alone examine their significance. Western aesthetic theories of the past few centuries also neglect everyday aesthetics because of their almost exclusive emphasis on art. In a ground-breaking new study, Yuriko Saito provides a detailed investigation into our everyday aesthetic experiences, and reveals how our everyday aesthetic tastes and judgments can exert a powerful influence on the state of the world and our quality of life